Sexual and Asexual Reproduction of Salix sitchensis and the Influence of Beaver (Castor canadensis) Herbivory on Reproductive Success. (5th November 2012) - Gerwing, Travis G.; Allen Gerwing, Alyssa M.; Rapaport, Eric; Alström-Rapaport, Cecilia
Abstract : The influence of beaver ( Castor canadensis Kuhl) herbivory on Salix reproduction, specifically the stimulation of asexual reproduction via browsed stem fragments, is relatively unknown. This study aimed to determine if beaver herbivory stimulates asexual reproduction of riparian willows and results in mature populations dominated by clones. The survival of seedlings and asexual propagules produced by beaver browse in populations of the riparian willow Salix sitchensis (Sanson in Bongard) were quantified to determine overwinter survival at 6 experimental sites. Salix sitchensis clonal diversity, using five microsatellite markers and the polymerase chain reaction, was calculated to detect if asexual reproduction had been stimulated by beaver herbivory. No sexual propagules survived overwinter in any of our study sites. Numerous asexual propagules were observed and 0–41% survived overwinter. Each sampled individual possessed a unique multilocus genotype, and clonal diversity was 1.0. Beaver herbivory did not create current willow populations dominated by clones. Beaver herbivory and asexual reproduction appeared to have played a minor role in the reproductive strategies of S. sitchensis at our sites in central British Columbia, Canada.